Insights on the value chain and management practices of stone pine forests in Lebanon - Sattout E.; Faour G. (Mediterranean pine nuts from forests and plantations, 2017)
Drawing the value chain of stone pine (Pinus pinea L.) forests (SPFs) in Lebanon requires defining habitat characteristics and vegetation composition, mapping stakeholders and forests governance structure, understanding local and international markets as well as collecting time series data on forests production and revenue. Remote sensing techniques and vegetation surveys were used to draw the ecological profile of SPFs. Information gathering on the extracted goods and annual cost and revenues of pine nuts resulted in a 20-years time series data (1996-2016). Data mining revealed limitations for the designed research study and prevailing narratives on the total annual production of pine nuts. Rapid appraisals with government representatives, land tenants and managers defined the existing administrative and management framework of these forests. The community of labors is regulated by the Order of Labors and Agriculture of SPFs. The workforce is mainly composed of foreigners with 400 forestland’s tenants. The average annual production generated from 6-years life cycle for pruning reaches up 1,100 t (metric ton) of pine nut kernel. The average local market price of pine nuts remaining higher than the imported one, increased from US$ 20 to 90 between 2000-2016. Turkey and Italy are the major importers of Lebanese pine nuts. The net revenue was estimated at US$ 37.8 million in 2012 and US$ 5.38 million in 1996. Since 2014, drop in the annual production was estimated at 500 t/year. The decrease in production is attributed to the Western Conifer Seed Bug (WCSB, Leptoglossus occidentalis). The insect has been affecting not only the annual production of nuts but also the land tenancy of SPFs.
2. International Meeting on Mediterranean Stone Pine for Agroforestry : AgroPine2016, 2016/05/18-20, Oeiras (Portugal)